Strategi Pemasaran Produk Bank Syariah Pada PT. Bank Sumut Syariah KCP Stabat - Sebayang, M. Irsan Khoir; Saleh, Muhammad; Sakdiah, Khairani (AGHNIYA : Jurnal Ekonomi Islam, 2023)
This study focuses on discussing marketing strategies in increasing the number of customers who use PT. Bank SUMUT Syariah KCP Stabat, after knowing the marketing strategy that was carried out, the writer will do a SWOT analysis. The research method used in this study is a descriptive qualitative research method with an empirical approach. In this study, researchers used a collection technique, namely by means of observation, interviews, and documentation. Data processing and analysis techniques are data reduction, data presentation, and drawing conclusions. The results of the study explain the marketing strategy carried out by PT. Bank SUMUT Syariah KCP Stabat cannot be separated from the elements of the marketing mix, which consist of: product strategy, place strategy, price strategy, and promotion strategy. Among these marketing strategies the most dominant is the promotion strategy which is carried out by means of advertising, sales promotion, personal selling, and direct marketing. In increasing the number of customers using PT. Bank SUMUT Syariah KCP Stabat conducts market segmentation, targeting, positioning and marketing mix. Based on the SWOT analysis it can be seen that PT. Bank SUMUT Syariah KCP Stabat has more advantages than weaknesses, therefore PT. Bank SUMUT Syariah KCP Stabat must be good at taking advantage of opportunities and defeating all threat factors to increase the number of customers.